Managerial capabilities of housing developers: building the competitive advantage of a firm. Issue 1 (2nd January 2016) - Jaafar, Mastura; Nuruddin, Azlan Raofuddin; Bakar, Syed Putra Syed Abu
Abstract : This paper investigates the internal factors, specifically the managerial capabilities, of Malaysian housing developers. Issues of strategic management in housing development have received limited attention from real estate industry commentators. In this qualitative study, 10 semi-structured snowball interviews were performed for the purposes of data collection. Categories of housing developer capabilities include business planning and strategy, marketing, project management, financial management, and networking. These interviews shed light on the capabilities of real estate practitioners. Given the small number of interviewees, the results of this study must be treated with caution, but should provide ample basis for future in-depth studies in this area. This study expands upon the current real estate literature, arguing that the intangible resources of a firm must be used in concert to sustain superior performance, and elucidates the effects of housing developers' managerial capabilities on the success of their business.